2017
DOI: 10.3892/ol.2017.5848
|View full text |Cite
|
Sign up to set email alerts
|

OVCA1 expression and its correlation with the expression levels of cyclin D1 and p16 in cervical cancer and intraepithelial neoplasia

Abstract: Abstract. The present study aimed to examine the associations between the protein and mRNA expression levels of ovarian cancer gene 1 (OVCA1), cyclin D1 and p16 and high-risk human papillomavirus (HR-HPV) infection in cervical lesions. The protein expression levels of OVCA1, cyclin D1 and p16 in 66 cases of cervical cancer, 64 cases of cervical intraepithelial neoplasia (CIN) and 34 normal cervix tissues were detected using immunohistochemistry. The mRNA expression levels of OVCA1, cyclin D1 and p16 in cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“… 15 and Tong et al . 18 recruited 15 and 6 ADC cases respectively and concluded Cyclin D1 as highly expressed invasion marker. Our results are in concordance with Balan et al .…”
Section: Discussionmentioning
confidence: 99%
“… 15 and Tong et al . 18 recruited 15 and 6 ADC cases respectively and concluded Cyclin D1 as highly expressed invasion marker. Our results are in concordance with Balan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike OVCA1, ectopic expression of OVCA2 in ovarian cancer cells does not suppress cell proliferation (Bruening et al, 1999). Accordingly, the tumor suppressor role of OVCA1 (DPH1), but not OVCA2, was highlighted in multiple studies (Chen and Behringer, 2004;Kong et al, 2011;Tong et al, 2017). OVCA1 and OVCA2 genes partially overlap but do not share coding regions and OVCA1 was not identified in our screen.…”
Section: Discussionmentioning
confidence: 78%
“…HPV DNA, E6/E7 mRNA p53, Rb, p16INK4a, telomerase RNA gene (TERC), serum SCC-Ag, OCVA1 [8,[10][11][12][13]15,[20][21][22][23][24][25][26] Markers of cell cycle and proliferation Ki-67, cyclin D1, p53, p63 [12,[26][27][28][29][30][31][32][33][34][35][36] Markers of apoptosis P53, BCL-2, BCL-XL, BAX [10,27,[37][38][39][40][41][42][43][44] Expression of cytokeratins-markers of differentiation CK7, CK8, CK17, CK19 [27,36,37,[45][46][47][48][49] Markers of cell adhesion, invasion and metastasis E-cadherin, P-cadherin, CD44, ADAM9, MT1-MMP, TIMP-1, TIMP-2, MT1-MMP, MMP-2, MMP-1, MMP-9, MMP-14, proMMP-14 furin, gelatinase, TIMP-1 and TIMP-2 [27,[50][51][52]…”
Section: Biomarkers Of Hpv Infection and Carcinogenesismentioning
confidence: 99%
“…Expression of cyclin D1 in CIN and cervical cancer was evaluated in comprehensive research on the relationship between the levels of immunohistochemical expression of protein and mRNA of ovarian cancer gene 1 (OVCA1), cyclin D1, and p16 and infection with high-risk human papillomavirus [26]. It was found that the expression of proteins OVCA1, cyclin D1, and p16 increased in CIN and cervical cancer.…”
Section: Markers Of Cell Cycle and Proliferationmentioning
confidence: 99%